Beyond Student Misconduct: A Literature Review on School Discipline, Teacher Modeling, and Social Attitude Formation - Dini Mulyani; Tri Gunawan; Sudrajat Sudrajat; Raras Gistha Rosardi (Indonesian Journal of Social Science Education (IJSSE), 2026)
This study aims to examine student misconduct in secondary education as a phenomenon shaped not solely by individual factors, but by the interaction of school discipline practices, teacher modeling, school culture, and hidden curriculum processes. Using a literature review approach, the study analyzes peer-reviewed journal articles published between 2015 and 2026, sourced from databases such as Scopus, ERIC, and Google Scholar. The selection focused on studies related to school discipline, teacher behavior, and social attitude formation, particularly within secondary education contexts. Data were analyzed using thematic analysis to identify recurring patterns and conceptual relationships across the literature. The findings indicate that contemporary scholarship increasingly conceptualizes discipline as a relational and developmental process rather than merely a mechanism of control. Teacher behavior plays a critical role in shaping student discipline by modeling the moral legitimacy of rules through daily interactions. In addition, school culture and hidden curriculum significantly influence students’ understanding of fairness, authority, and social norms. Supportive and consistent disciplinary environments are associated with positive outcomes such as empathy, responsibility, and social engagement, while punitive and inconsistent practices tend to produce alienation and negative attitudes. Overall, the study highlights that student misconduct is structurally influenced, requiring integrated, whole-school approaches to discipline reform. This study contributes by offering an integrative framework that links discipline, teacher modeling, and school culture as a unified system of social attitude formation.